Remediation of Caffeine from Aqueous Solutions Using Waste-Derived Adsorbents: A Polyaniline/Cuttlefish Bone Nanocomposite for Pollutant Removal - Esraa Salama; Samar M. Mahgoub; Ahmed A. Allam; Haifa E. Alfassam; Rehab Mahmoud (Colloids and Interfaces)
Caffeine is commonly used in pharmaceutical and personal care products, where it serves both therapeutic and cosmetic purposes. However, its widespread presence in wastewater from the pharmaceutical and cosmetic industries has raised concerns about environmental contamination. This study explores the use of a polyaniline (PANI)/cuttlefish bone (CB) nanocomposite as an effective adsorbent for the removal of caffeine from aqueous solutions. The nanocomposite was synthesized by incorporating polyaniline (PANI) onto cuttlefish bone (CB) flakes, resulting in a material with a hybrid morphology consisting of layered nanosheets and flaky structures. Adsorption experiments were conducted to determine the optimal conditions for caffeine removal, with results showing the best adsorption efficiency at pH 7 and an adsorbent dosage of 0.1 g/L for the nanocomposite, achieving an 80.73% removal efficiency. The maximum adsorption capacity of the nanocomposite was 108.33 mg/g—significantly higher than for pure CB (55.05 mg/g) and PANI (57.71 mg/g). The adsorption process followed the pseudo-second-order kinetic model and the Langmuir isotherm, indicating a chemisorption mechanism and monolayer adsorption. Additionally, the nanocomposite demonstrated excellent reuse capacity, maintaining over 85% of its initial efficiency after multiple adsorption–desorption cycles, highlighting its potential for sustainable long-term use. This work demonstrates the potential of using waste-derived materials like cuttlefish bone as an effective support for PANI in the development of low-cost, sustainable adsorbents for pollutant remediation in pharmaceutical wastewater. Future studies will explore the adsorbent’s applicability for other contaminants and its potential antimicrobial properties.